Tinjauan Hukum Internasional terhadap Status Organisasi Papua Merdeka (OPM) sebagai Subjek Hukum Internasional - Wendra, Muhammad; Sutrisno, Andri; Kamal, Muhammad Refly (Journal of Contemporary Law Studies, 2025)
This study aims to present the implications of separatist movements that are recognized as international subjects, especially for the parent country. This study is urgent due to the importance of the status of separatist groups as subjects of international law and its impact on the parent country. This study uses a normative juridical method with a literature study approach that includes doctrine and various other international legal conventions. The results of the study show that separatist movements generally demand separation from the parent country based on various backgrounds, such as ideological and racial differences, as well as injustices or human rights violations. To achieve this goal, separatist groups need international support, such as recognition as subjects of international law through the determination of belligerent status or geopolitical recognition to facilitate their goals. Therefore, this study shows that in order to achieve the status of an international legal subject, separatist movements not only require various specific criteria as stipulated in international law, but also require factors such as international politics to achieve these goals. Furthermore, this study also shows that such recognition can have significant political, diplomatic, and social implications for the parent country, such as Indonesia. The influence of recognizing the OPM as a subject of international law theoretically and juridically has a significant impact on the parent country, such as Indonesia, including challenges to Indonesia’s sovereignty and territorial integrity, a negative international precedent for Indonesia regarding separatism, disruption of the country’s development and security (stability), and vulnerability to negative impacts in conducting international relations.